The Influence of Intellectual Intelligence on Performance through Job Satisfaction among Employees of Bank Syariah Indonesia, Soekarno Hatta-Malang Branch - Wardani, Wiwit Setyo (Journal of Economics and Social Sciences (JESS), 2025)
It utilizes job satisfaction as an intermediary variable to study the correlation of intellectual intelligence and employee performance. It is a quantitative associative causal research. 36 people constitute the total sample in the research, which was carried out at the Bank Syariah Indonesia Soekarno Hatta Malang Branch. The methods that are employed are linear regression analysis and path analysis. The findings on that research plainly suggest that while job satisfaction influence performance, intellectual competence has no effect on job satisfaction. However, compared to the direct influence, the indirect impact of intellectual intelligence on performance through job satisfaction is much lesser